education, students; informatization; information and communication technologies (ICT); physical culture, competencies - Yu. Zhuravleva; M. Katrenko (Вестник Северо-Кавказского федерального университета)
The article considers the problem of using IR technologies (ICT) by university teachers in the field of physical culture. Analysis of literary sources, survey, questioning, method of mathematical data processing, the scientific works of domestic scientists, legislative materials affecting the development of digital competence of teachers in the context of digital transformation of education were analyzed; the need to develop ICT skills among teachers is substantiated, since innovative processes predetermine fundamental changes and increase the requirements not only for the system of training specialists, but also for the skills of the teacher, for his individual level of mastering ICT; the position of the teacher is determined as a carrier of knowledge that he shares with students and as a conductor capable of using ICT tools in the educational process, including the skills of searching, exchanging information, communication; the directions of application of information and communication technologies in the field of physical culture are considered, on the example of the implementation of additional practical classes in the online format; the main reasons for the lack of digital competence of teachers are established, as well as possible ways to solve this problem; groups of software tools are allocated to perform specific tasks of distance learning; author's developments for the implementation of elective disciplines in physical culture and sports in remote access are proposed; empirical research methods were applied, which made it possible to assess the state of the problem. The dynamics of mastering communication technologies by teachers of physical culture is clearly presented, which contributed to the increase in educational motivation and motor activity of students.